DERAJAT KRISTALISASI SEBAGAI FUNGSI WAKTU AGEING DAN WAKTU KRISTALISASI PADA SINTESIS ZEOLIT A DENGAN RADIASI GELOMBANG MIKRO - Wuntu, Audy D.; Tangkuman, Herling D. (Sam Ratulangi University, 2008)
A-type zeolite has wide application in the field of catalysis and adsorption in industry and daily use as well. This material in a kind of synthetic material and can be synthesized from various raw materials and using various method, one of which is conventional hydrothermal condition. The use of microwave is one of the methods that can reduce the time needed for A-type zeolite synthesis. In this research, the power of the microwave is set to 720 Watt with ageing time of 0 hour and period of synthesis is set at the range of 0 to 50 minutes. Characterization of the zeolite synthesized using microwave was performed using infra red spectroscopy and the result was compared to that synthesized at conventional hydrothermal condition. The results showed that conventional hydrothermal condition at 0 hour ageing time and 5 hours crystallization period gave zeolite more crystallized than that resulted using microwave. The period of zero to 50 minutes crystallization time at microwave did not result in crystallized zeolite.